Altered ocular surface microbiota in obesity: a case-control study - Liang, Chenghong; Wang, Limin; Wang, Xiudan; Jia, Yifan; Xie, Qinyuan; Zhao, Lingyun; Yuan, Huijuan (Frontiers in Cellular and Infection Microbiology, 2024)
This study aimed to investigate the composition of ocular surface microbiota in patients with obesity. Methods This case-control study, spanning from November 2020 to March 2021 at Henan Provincial People's Hospital, involved 35 patients with obesity and an equivalent number of age and gender-matched healthy controls. By employing 16S rRNA sequencing, this study analyzed the differences in ocular surface microbiota between the two groups. The functional prediction analysis of the ocular surface microbiota was conducted using PICRUSt2. Results The alpha diversity showed no notable differences in the richness or evenness of the ocular surface microbiota when comparing patients with obesity to healthy controls (Shannon index, P=0.1003). However, beta diversity highlighted significant variances in the microbiota composition of these two groups (ANOSIM, P=0.005). LEfSe analysis revealed that the relative abundances of Delftia, Cutibacterium, Aquabacterium, Acidovorax, Caulobacteraceae unclassified, Comamonas and Porphyromonas in patients with obesity were significantly increased (P<0.05). Predictive analysis using PICRUSt2 highlighted a significant enhancement in certain metabolic pathways in patients with obesity, notably xenobiotics metabolism via cytochrome P450 (CYP450), lipid metabolism, and the oligomerization domain (NOD)-like receptor signaling pathway (P<0.05). Conclusions Patients with obesity exhibit a distinct ocular surface core microbiome. The observed variations in this microbiome may correlate with increased activity in CYP450, changes in lipid metabolism, and alterations in NOD-like receptor signaling pathways.